OPTIMASI SODIUM STARCH GLYCOLATE DAN POLYVINYLPYRROLIDONE K-30 DALAM SEDIAAN ORALLY DISINTEGRATING TABLET SALBUTAMOL SULFAT - Budipratiwi Wisudyaningsih; Lusia Oktora Kumala Sari; Tiara Puspita Arisanti (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2023)
ABSTRACT Difficulty in swallowing drug and slow onset of action of drug are common problems of conventional tablet. Orally disintegrating tablet (ODT) is an innovative dosage form to overcome the problem of swallowing drug and provide quick onset of action of drug because it can disintegrates quickly when contact with saliva in less than 3 minutes. This study formulate and evaluate ODT containing salbutamol sulphate to relieve the respiratory disorders immediately. Materials that affect the disintegration time of ODT are superdisintegrants and binders. Sodium Starch Glycolate (SSG) is a superdisintegrant that has high swelling capacity and its efficiency is not affected by compression and hydrophobic materials. PVP K-30 is a water soluble binder that effective to increase hardness and decrease friability of ODT without prolonging the disintegration time. The aim of this study is to optimize SSG and PVP K-30 to get the optimum formula of ODT salbutamol sulphate. ODT salbutamol sulphate was made by direct compression method. The optimization was carried out using two-level and two-factor of factorial design. Disintegration time, hardness, and friability of ODT were responses that evaluated to get the optimum formula of ODT salbutamol sulphate. The result showed that SSG affected in increasing of disintegration time of ODT. PVP K-30 affected in increasing of disintegration time, decreasing friability, and increasing hardness of ODT. The optimum formula contained 4% of SSG and 1,5% of PVP K-30 resulted in 37,58 seconds of disintegration time, 4,713 kg/cm2 of hardness, and 0,6298% of friability. The optimum formula dissolved 92.296 % after 30 minute. Keywords : Orally disintegrating tablet; salbutamol sulphate; SSG; PVP K-30